Pengaruh Edukasi Cakram Asupan Makan dan Cairan Atlet terhadap Pengetahuan dan Sikap terkait Gizi pada Atlet di SSB Baturetno - Wahyuningsih, Siti; Afriani, Yuni; Puspaningtyas, Desty; Dewi, Mutiara Tri Buana Tungga; Sari, Siska Puspita (Universitas Airlangga, 2025)
Background: Athlete performance in Indonesia is often hindered by inadequate nutrient intake. The nutritional intake of athletes is influenced by their knowledge of nutrition. The knowledge and attitudes of athletes regarding nutritional needs can be enhanced through the educational media of the Cakram Asupan Makan dan Cairan Atlet. Objective: To determine the effect of education using the Cakram Asupan Makan dan Cairan Atlet on athletes' knowledge and attitudes related to nutrition. Methods: A quasi-experimental study with a one-group pretest-posttest design was used in this research. A total of 33 adolescent athletes aged 13-15 years from SSB Baturetno were selected as respondents using accidental sampling. Data were collected through a validated questionnaire, with interventions conducted twice a week. The Paired Sample T-test was used to analyze the pre-test and post-test I knowledge data, while the Wilcoxon Rank Test was applied for the pre-test and post-test II knowledge, as well as all tests on attitude scores. Results: The average pre-test knowledge score is 6.61±1.903. The average post-test I knowledge score is 9.18±2.833, and the median post-test II knowledge score is 10 (range 5-14). The median pre-test attitude score is 10 (range 4-14), with median post-test I and II attitude scores being 11 (range 4-14) and 12 (range 6-14), respectively. There was an effect of education on knowledge with p1<0.001; p2<0.001; p3=0.06. There was an effect of education on attitude with p1=0.014; p2<0.001; p3=0.369. Conclusions: There was an influence of the education using Cakram Asupan Makan dan Cairan Atlet on athletes' knowledge and attitudes towards nutrition.